Особенности русского языка как унаследованного в Германии - Brüggemann, Natalia (Przegląd Rusycystyczny, 2018)
The purpose of the article is to give an outline of the main features of the Russian heritage language used by the second generation of immigrants in Germany with regard to particular teaching needs. I will present those phenomena as attrition, incomplete acquisition, matter and pattern borrowing, the role of parents’ input etc. and develop several requirements meant for curricula for teaching in universities and for the conception of lessons particularly devoted to heritage speakers.